Therapeutic Strategies for Cancer in Late Antiquity: Evidence From Aetius of Amida’s Medical Compendium - Orlov Vilimonović, Larisa (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2026)
This article examines the therapeutic management of malignant disease in the medical compendium of Aetius of Amida, treating the Tetrabiblon as evidence for late antique medical practice rather than merely as a repository of inherited theory. Focusing on passages concerning breast and uterine carcinomas, it analyzes diagnostic description, surgical criteria, post-operative care, and pharmacological treatment. The article argues that Aetius preserves a coherent therapeutic framework in which prognosis, anatomical accessibility, and humoral regulation determine the choice between excision, cauterization, and palliative care. The study further shows that Aetius’ pharmacological material, combining botanical, mineral, and animal-derived substances, reflects a practical and symptom-oriented approach to malignant disease. It suggests that late antique physicians possessed a more nuanced practical understanding of tumor progression and therapeutic limits than is often assumed.